Balancing Migration: Overcoming the challenge to SaaS provisioning for core business activities: A South African case study - Manjo, Sherwin (Department of Information Systems, 2018)
Cloud computing provides shared information and communication technology (ICT) resources to individuals and organisations, including hardware and software resources that were previously too costly for an individual organisation to manage and own. Cloud computing makes vast amounts of ICT resources available to business organisations, resources that can improve business processes and allow business organisations to leverage ICT in ways that were previously impossible. The correct implementation, adoption and usage of ICT within a business organisation can lead to enhancements in productivity, innovation, and new products and services, as well as the reduction of production costs. Recent literature has attested to the fact that the adoption of cloud computing has been much lower than expected. Business organisations that have adopted cloud computing have done so mainly in products and services that can be categorised as support or non-core activities, such as HR, accounting, and marketing. In order to understand why the adoption pattern of cloud computing in business organisations has focused mainly on non-core activities, this study aims to identify the core challenge facing cloud service providers (CSPs) that provision cloud solutions to business organisations in the investment management industry. These would include cloud solutions that investment managers can use in their core business activities. Furthermore, the aim of this dissertation is to identify how CSPs overcome the core challenge faced. A case study was performed on a single CSP that provisions a SaaS solution to the investment management sector in South Africa. The case study identified migration as the core challenge experienced by CSPs. Classical grounded theory was used to generate the theory of “Balancing Migration” being the resolution to the core challenge identified. The results of the study point to the fact that investment management organisations have processes and systems that have become entrenched in their business over many years. Migrating an established system to the cloud is more than just substituting software. Migration to the cloud requires investment managers to migrate both business processes and operating strategy, and to migrate the actual software products and infrastructure. A CSP provisioning a SaaS solution for a core business activity needs to migrate the products that they offer as well as their business strategy. The theory of “Balancing Migration” proposes that these four categories of migration challenges need to be addressed simultaneously and holistically. In summary, “Migration” is the core concern to a CSP provisioning a SaaS solution for a core business activity, and “balancing migration” is how this core concern is resolved.